Bagaimana Minat Beli Motor Honda Scoopy Di Dealer PT. Astra International Cabang Kolaka? - Albar Albar; Niar Astaginy; Hanif Kurniadi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2023)
This research uses a quantitative descriptive method approach. Data collection in this research used observation and questionnaires. The population in this research is consumers who have purchased a Honda Scoopy motorbike at the Kolaka Honda Motorcycle Dealer. The sample in this study amounted to 130 people. The data analysis techniques used in this research are validity testing, reliability testing, classical assumption testing and multiple linear regression analysis using the SPSS program. Based on the research results, it is known that (1) There is an insignificant influence between lifestyle on interest in buying a Honda Scoopy motorbike at the Kolaka Motorcycle Sales Dealer; (2) There is an insignificant influence between innovative product design on interest in purchasing Honda Scoopy motorbikes at Kolaka Motorcycle Sales Dealers; (3) There is a positive and significant influence between price perception on interest in buying a Honda Scoopy motorbike at the Kolaka Sales Motorcycle Dealer; and (4) There is a significant influence between lifestyle, innovative product design and price perception on interest in purchasing a Honda Scoopy motorbike at the Kolaka Sales Motorcycle Dealer.